Association of ET1 and APE1 Genes Polymorphism with Coronary Artery Disease - Raza, Syed T.; Eba, Ale; Wani, Irshad A.; Srivastava, Sanchita; Mahdi, Farzana (International Journal of Angiology, 2024)
Coronary artery disease (CAD) is one of the most common cardiovascular diseases (CVDs), being the foremost reason for mortality and disability globally. It is a cascade of polygenic architecture of various disorders as a resultant of complexities between various genetic factors and environmental factors. The aim of the present study was to investigate whether the ET1 and APE1 gene polymorphism is associated with the susceptibility to CAD. This study was approved by the Ethical Review Committee of Era Medical College and Hospital. Three milliliters of venous blood sample was collected in ethylenediaminetetraacetic acid-coated vials, and genomic DNA was isolated by using the standard phenol-chloroform extraction method for restriction fragment length polymorphism-polymerase chain reaction study. The APE1 gene AA, AG, GG, and AG + GG genotypes frequencies were 13.91, 40.87, 45.22, and 86.99% in CAD cases and 13, 50, 37, and 87% in controls, respectively. The ET1 gene GG, GT, TT, GT + TT genotypes frequencies were 6.67, 37.5, 55.8, and 93.34% in CAD cases and 6.67, 25.33, 68, and 93.34% in controls. The ET1 and APE1 gene polymorphisms were not significantly associated with the risk of CAD.
Keywords: coronary artery disease; endothelin 1; apurinic/apyrimidinic endonuclease 1; gene polymorphism